SPEECH ACTS AND MEANING OF LANGUAGE ON DEDDY CORBUZIER’S PODCAST - Yoga Pratama, Ngurah Artha; Septiana, Kadek Ayu Kartika; Sari Dewi, Ayu Kartika (IKIP SARASWATI TABANAN, 2024)
The title of this research is Speech Acts and Meaning of Language on Deddy Corbuzier's Podcast. This study discusses the form of speech acts, functions of speech acts, and the meaning of speech acts on the podcast. The theory used in this study is the theory of Austin (1962) to discuss the form of speech acts. Meanwhile, Searle's theory (1969) discusses the function and meaning of speech acts. In this study, the data source used was Deddy Corbuzier's podcast which was selected randomly, at the time of data collection using the listen and note method. The data that has been collected is then classified based on the form of the speech act, the function of the speech act, and the meaning of the speech act. From the results of the analysis found the form of speech acts locutionary, illocutionary, and perlocutionary. Meanwhile, the function of speech act found is expressive speech act function, directive speech act function, commissive speech act function, declarative speech act function, and representative speech act function.